Project Portfolio Management with the support of the AHP Method - Resende Loureiro, Rodrigo (2018)
Project Portfolio Management (PPM), fundamental for companies to adapt to the scenarios and achieve their strategic objectives, requires the use of a tool to aid decision making in the selection of projects. This study aimed to present a theoretical example of PPM, using the Analytic Hierarchy Process (AHP), as a strategy to justify the decision. It was implemented with the support of a well-known and widely available spreadsheet, avoiding the use of proprietary software. It is concluded that the proposed model is feasible and, based on the resources available in it - sensitivity and consistency analysis, the different aspects of the PMM can be more easily verified, allowing the decision-maker to not just determine and justify its decision-making, but to learn and improve their decision-making process.